2022
DOI: 10.1049/ipr2.12497
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐scale GAN with residual image learning for removing heterogeneous blur

Abstract: Processing images with heterogeneous blur remains challenging due to multiple degradation aspects that could affect structural properties. This study proposes a deep learning‐based multi‐scaled generative adversarial network (GAN) with residual image learning to process variant and in‐variant blur. Different scaled images with corresponding gradients are concatenated as a multi‐channel single input for the proposed GAN. Residual‐ and dense‐networks are combined to explore salient features in the bottleneck sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…A GAN-based deep-learning model [13][14][15][16][17] was used to reduce speckle noise and improve the spatial resolution of orthographic view images extracted from holograms. The GAN model is a generative model that produces realistic images and human-like text.…”
Section: Network Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…A GAN-based deep-learning model [13][14][15][16][17] was used to reduce speckle noise and improve the spatial resolution of orthographic view images extracted from holograms. The GAN model is a generative model that produces realistic images and human-like text.…”
Section: Network Architecturementioning
confidence: 99%
“…In the proposed method, holograms are generated using two-dimensional image data for deep-learning model training, and a dataset is constructed by applying bandpass filtering. A generative adversarial network (GAN)-based deep-learning model [13][14][15][16][17] was designed to improve the quality of the extracted light-field data and was trained using the dataset. Finally, using the trained model, light-field data with reduced speckle noise and improved spatial resolution were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that a captured image of a real scene or object can be degraded by inaccurate capture and optical factors such as improper depth of field, poor focus, camera shake, object movement, short exposure, and poor optical quality. Tasks involving image identification or classification can be impeded by noisy visuals with imperfections [2]. Noise often comes out in images as detached pixels or blocks of pixels, causing heavy visual effects.…”
Section: Introductionmentioning
confidence: 99%